Kajian Etnobotani Tanaman Berkhasiat Obat di Desa Cipacing Kecamatan Jatinangor Kabupaten Sumedang Jawa Barat (International Forum of Researchers and Lecturers, 2023)
Cipacing Village, Jatinangor District, Sumedang Regency is an area that has extensive plantation land and rice fields. This village is still beautiful with lush green trees and vast fields which are its own attraction. Many people in Cipacing Village still use plant species to treat diseases. The aim of this research is to identify the use and utilization of medicinal plants in Cipacing Village. This type of research is descriptive with qualitative research methods. Sampling was carried out using purposive sampling technique. Data collection was obtained from the results of semi-structured interviews. There were 30 respondents in this study who were described by characteristics such as gender, age and level of education. Based on research conducted, the plants used as medicine by the community are 23 families, 28 genera and 29 species with the dominant family being Zingiberaceae (26%) and the co-dominant family being Piperaceae (8.7%). The highest habitus was found in herbaceous plants (40%) while the part of the plant that was widely used was the leaves (57%). The most dominant plant processing used is by boiling the leaves and then filtering the boiled water for drinking.